Pengaruh model pembelajaran multiliterasi terhadap keterampilan berpikir kritis ditinjau dari self regulated learning mahasiswa - Milenia Suci Rachmawati; Idam Ragil Widianto Atmojo; Roy Ardiansyah (Didaktika Dwija Indria, 2023)
As a teacher candidate, it is important for a student to master the 21st century skills, namely the 4C. Critical thinking is one of the directions of 21st century education. As prospective educators, students need to master critical thinking skills which are supported by good self-regulated learning as a provision so that later they are able to conduct meaningful learning in class. This study aims to determine the effect of applying the multiliteracy learning model on students' critical thinking skills in terms of the students' self-regulated learning. The type of research method used is a quantitative experiment with a 2 x 3 factorial design. Based on the results of hypothesis testing using the two-way ANOVA test with different cells, the results are Fobs > Fα  with details, namely Fa > Fα (18,03901 > 3,986269479), Fb > Fα (27,5862 > 3,135917934), and Fab > Fα(139,2992 > 3,135917934). Referring to these results, it can be seen that the multiliteracy learning model has an effect on students' critical thinking skills, self-regulated learning has an effect on students' critical thinking skills, and there is an interaction between the multiliteracy learning model and the level of self-regulated learning on critical thinking skills.